PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PENGGUNA JASA HOTEL BINTANG TIGA DI KOTA AMBON - Waelauruw, Anthoneta Telsy (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
This study aimed to determine the effect of service quality on customer satisfaction service usersthree-star hotel in the city of Ambon. Data was collected using questionnaires to 100 respondentswho are the sample of the study population were taken by non-probability sampling method withconvenience sampling technique. Collected data were analyzed using multiple regression analysisof quantitative methods. The results showed that the quality of service simultaneously and partiallypositive and significant impact on consumer satisfaction service users three-star hotel in the city ofAmbon. Therefore, it is suggested that the management of each of the three star hotels canconstantly improve the quality of services, among others, by providing the opportunity foremployees to participate in education and training relevant to their job duties.Keywords: service quality, customer satisfaction